2010
DOI: 10.1002/ijc.24689
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lycopene and tomato extract supplementations inhibit nonalcoholic steatohepatitis‐promoted hepatocarcinogenesis in rats

Abstract: Epidemiological and experimental studies provide supportive evidence that lycopene (LY), a major carotenoid from tomatoes and tomato products, may act as a chemopreventive agent against certain types of cancers. We recently showed that high-fat diet (HFD)-induced nonalcoholic steatohepatitis (NASH) promoted diethylnitrosamine (DEN)-initiated hepatocarcinogenesis in a rat model. Using this model, we investigated the efficacy of an equivalent dosage of dietary LY from either a pure compound or a tomato extract (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 44 publications
8
98
1
2
Order By: Relevance
“…They also concluded that lycopene's chemopreventive effects were due to its modulating effect on the liver enzyme activating DENA, namely CYP2E1. Three other research groups [155,181,184] conducted their studies using several chemical hepatocarcinogenesis model and observed similar end points as Astorg et al [154] . All three research groups observed the chemopreventive effects of lycopene on hepatocellular carcinogenesis induced by DENA in rats as indicated by inhibition of GSTp foci.…”
Section: Rj Et Al Terpenoids and Liver Cancermentioning
confidence: 61%
See 2 more Smart Citations
“…They also concluded that lycopene's chemopreventive effects were due to its modulating effect on the liver enzyme activating DENA, namely CYP2E1. Three other research groups [155,181,184] conducted their studies using several chemical hepatocarcinogenesis model and observed similar end points as Astorg et al [154] . All three research groups observed the chemopreventive effects of lycopene on hepatocellular carcinogenesis induced by DENA in rats as indicated by inhibition of GSTp foci.…”
Section: Rj Et Al Terpenoids and Liver Cancermentioning
confidence: 61%
“…All three research groups observed the chemopreventive effects of lycopene on hepatocellular carcinogenesis induced by DENA in rats as indicated by inhibition of GSTp foci. Wang et al [184] confirmed the efficacy of lycopene against nonalcoholic steatohepatitis (NASH)-promoted hepatocarcinogenesis and provided several molecular mechanisms, such as lowering of protein expression of proliferating cell nuclear antigen, cyclin D1, and NF-κB as well as induction in nuclear NF-E2 related factor-2 and heme oxygenase-1 protein expressions. The efficacy of tomato extract (TE) as a chemopreventive agent against DENA-initiated NASHpromoted hepatocarcinogenesis in male rats was also investigated.…”
Section: Rj Et Al Terpenoids and Liver Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…These compounds can counteract hepatocyte injury associated with lipid peroxidation and chronic oxidative stress. Some authors have reported a positive effect of dietary antioxidants such as vitamins C and E [5,6], bioactive compounds like resveratrol [7] and lycopene [8,9], and antioxidant drugs such as N-acetylcysteine [10] on the biomarkers of NAFLD, as well as highlighting that they impede progression toward NASH in both human and animal models. Tomatoes are characterized by a low fat and protein content, and are rich in phenolic compounds, carotenoids, and vitamins C and E [11,12].…”
Section: Introductionmentioning
confidence: 97%
“…Several epidemiological and experimental studies have demonstrated beneficial effect of lycopene on preventing HCC [129][130][131]; for example, lycopene-rich diet significantly inhibited DEN-initiated and NASH-promoted early hepatocarcinogenesis in rats, which was associated with decreased expression of cyclin D1, as well as inhibition of ERK1/2 and NF-kappaB activities independently of apoptosis [132]. The accumulated literature suggests the possibility that higher consumption of tomato products or lycopene is safe and may have potential benefits for lowering the risk of cancer including HCC; however, further research is necessary to draw definitive conclusions.…”
Section: Lycopenementioning
confidence: 98%